2022
DOI: 10.1186/s43055-022-00832-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of chest CT severity score with clinical parameters in COVID-19 pulmonary disease in a tertiary care hospital in Delhi during the pandemic period

Abstract: Background Since November 2019, the rapid outbreak of coronavirus disease 2019 (COVID-19) has become a public health emergency of international concern. COVID-19 disease is caused by a new variant of coronavirus, named as ‘severe acute respiratory syndrome coronavirus 2.’ Chest CT has a potential role in the diagnosis, detection of complications and in predicting clinical recovery of patients or progression of coronavirus disease 2019. Degree and severity of lung involvement can be assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…2 In the present study, TLC was increased in 35% of cases and showed a positive correlation (r=0.07) with CT severity score. Similar studies done by Sharma S. et al 3 and Agarwal N et al 4 showed increased TLC count in 48.7% and 39.03% respectively, concluding a rising trend of leukocyte counts with increasing disease severity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…2 In the present study, TLC was increased in 35% of cases and showed a positive correlation (r=0.07) with CT severity score. Similar studies done by Sharma S. et al 3 and Agarwal N et al 4 showed increased TLC count in 48.7% and 39.03% respectively, concluding a rising trend of leukocyte counts with increasing disease severity.…”
Section: Discussionsupporting
confidence: 81%
“…25) with CT severity score. Similar studies have been done by various other authors, Sharma S. et al, 3 Ahmad Z et al 6 , Xie Y et al 7 Agarwal N et al, 4 Chandran J et al 5 indicating that when the absolute lymphocyte count decreases, the patient's condition also deteriorates.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The patients were then classified into three groups according to their severity based on the OAB symptom scoring system, as follows: 3-5: mild, 6-11: moderate, and >12: severe (Table 1 ). Similarly, patients were also classified into three groups based on the CT severity scoring system for lung involvement due to COVID-19 infection, as follows: <8/24: mild, 9-15/24: moderate, and >15/24: severe [ 11 ]. The three lung lobes on the right and two lobes on the left were individually assessed, and the percentage involvement of the lobe was noted based on visual assessment.…”
Section: Methodsmentioning
confidence: 99%